Periprosthetic Joint Infection: The Unending Journey - Anyaehie, Udo Ego; Muoghalu, Obiora Nonso; Onuminya, John Enekele (Nigerian Journal of Orthopaedics and Trauma, 2020)
Periprosthetic joint infection (PJI) is one disaster too many and will remain a never‑ending topic as long as joints are replaced all over the world. The objective was to review current literatures on the pathology, management and prevention of PJI. This is a descriptive review of the current literatures on the definition, epidemiology, risk factors, pathology, classification, diagnosis, treatment and prevention of PJI. PJI is one of the most common causes of revision arthroplasty with increasing incidence. The risk factors are patient, staff and environmental mediated, and they are grouped into modifiable and non‑modifiable risk factors. The modifiable risk factors are controllable. In general, PJI can be early or late, and this provides a guide to treatment. Arriving at a diagnosis can be clinical, laboratory, radiological or a combination, with newer trends geared towards identifying the exact organism causing the infection. Preventing PJI is the goal of every arthroplasty surgeon. The diagnosis of PJI remains a problem, and the optimal method of treatment is a subject of debate. Therefore, preventive measures should be topmost on every surgeon’s mind.